Impact of foreign aid and foreign direct investment on economic growth: evidence from Sub-Saharan African countries - Masoud Rashid Mohamed,; Shivee Ranjanee Kaliappan,; Normaz Wana Ismail,; Azman-Saini, W. N. W (Penerbit Universiti Kebangsaan Malaysia, 2014)
The purpose of this study is to examine the impact of foreign aid and FDI on economic growth of Sub-Saharan African countries. The generalized method of moments is applied on 41 countries covering the period of 1998 to 2010. The results suggest that while foreign aid has negative effect on growth, the impact of FDI is positive but statistically insignificant. Furthermore, we found evidence that foreign aid from different bilateral donors may have different effects on economic growth.